Legal Protection of Women's Rights in the Division of Joint Assets Due to Divorce - Watiah, Watiah; Hafidz, Jawade (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
This study aims to analyze: 1)The status of joint property between husband and wife after divorce. 2) Forms of legal protection for women's rights in the division of joint property after divorce. This type of research is normative legal research. The approach method in this research is a statute approach. The type of data in this study is secondary data sourced from primary, secondary, and tertiary legal materials. The data collection method uses library techniques (document study). The analysis in this study is prescriptive. The results of the study conclude: 1) The status of joint assets between husband and wife after divorce remains legally recognized as joint property until a legal division is carried out according to statutory provisions. This division is basically carried out in a balanced manner (½:½) as stipulated in Article 97 of the Compilation of Islamic Law and Article 128 of the Civil Code, but the judge has the authority to assess substantive justice based on the contribution of each party. Theoretically, this principle is in line with Gustav Radbruch's Theory of Justice which places justice as the highest legal value, and is in line with the values of Pancasila justice and Islamic justice which emphasize balance, welfare, and humanity. 2) Forms of legal protection for women's rights in the division of joint assets after divorce include preventive protection and repressive protection. Preventive protection is realized through a marriage agreement, the obligation of joint agreement in the management of joint assets, as well as recording and monitoring assets to prevent unilateral control. Repressive protection is provided through the woman's right to file a lawsuit for the division of joint property, demand the annulment of unilateral legal acts, and acknowledge the wife's non-material contributions, as stipulated in PERMA Number 3 of 2017 and affirmed in several Supreme Court decisions. Support from various regulations such as Law Number 7 of 1984 concerning the Ratification of CEDAW, Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence further strengthens the guarantee of women's economic rights after divorce.